2022
DOI: 10.3389/fcvm.2022.996467
|View full text |Cite
|
Sign up to set email alerts
|

Red meat consumption and risk for dyslipidaemia and inflammation: A systematic review and meta-analysis

Abstract: AimThe study (PROSPERO: CRD42021240905) aims to reveal the relationships among red meat, serum lipids and inflammatory biomarkers.Methods and resultsPubMed, EMBASE and the Cochrane databases were explored through December 2021 to identify 574 studies about red meat and serum lipids markers including total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), C-reactive protein (CRP) or hypersensitive-CRP (hs-CRP). Finally, 20 randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…We found that triglycerides in seven lipoprotein subclasses (very small VLDL, IDL, large LDL, LDL, medium LDL, small LDL, and very large HDL) were positively associated with both red meat consumption and IHD mortality. Our findings are consistent with previous intervention studies that continuous consumption of red meat, such as pork and beef, affected plasma triglyceride levels [25,26]. Triglycerides are major components of triglyceride-rich lipoproteins (TRLs).…”
Section: Discussionsupporting
confidence: 92%
“…We found that triglycerides in seven lipoprotein subclasses (very small VLDL, IDL, large LDL, LDL, medium LDL, small LDL, and very large HDL) were positively associated with both red meat consumption and IHD mortality. Our findings are consistent with previous intervention studies that continuous consumption of red meat, such as pork and beef, affected plasma triglyceride levels [25,26]. Triglycerides are major components of triglyceride-rich lipoproteins (TRLs).…”
Section: Discussionsupporting
confidence: 92%
“…One cut of meat may be considered leaner than another; according to the United States Department of Agriculture (USDA), 3.5oz or 100g of lean meat, such as a cut of top sirloin steak or chicken breast without the skin, contains less than 10g of total fat, 4.5g of saturated fat and 95mg of cholesterol. A systematic review and meta-analysis which investigated 20 randomized control trials with a total of 1001 adults showed that increased red meat consumption resulted in increased serum lipid concentrations but ultimately had no significant effects on hs-CRP (Sun et al, 2022). However, excessive consumption of red meats high in saturated fatty acids may disrupt lipid metabolism, which can lead to increased secretion of CRP or hs-CRP (Saltiel and Olefsky, 2017;Sun et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis which investigated 20 randomized control trials with a total of 1001 adults showed that increased red meat consumption resulted in increased serum lipid concentrations but ultimately had no significant effects on hs-CRP (Sun et al, 2022). However, excessive consumption of red meats high in saturated fatty acids may disrupt lipid metabolism, which can lead to increased secretion of CRP or hs-CRP (Saltiel and Olefsky, 2017;Sun et al, 2022). Additionally, increased lipid metabolism disruption may lead to oxidative stress, which can further induce inflammation (Leroy and Cofnas, 2020;Sun et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in dietary habits of AA and whites are important risk factors for diabetes. Certain dietary behaviors, such as a high intake of red meat, have been associated with Type II diabetes and increased TG levels [108,109]. Since dietary patterns were not assessed, we are unable to say that the variance in the TG levels between the two groups was not due to a difference in their diet.…”
Section: Limitations Of the Studymentioning
confidence: 92%